1996
DOI: 10.1002/(sici)1097-0061(19960915)12:11<1125::aid-yea7>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Gene Encoding a G Protein α Subunit Involved in the Regulation of cAMP Levels in the Yeast Kluyveromyces lactis

Abstract: Using chromosomal DNA from Kluyveromyces lactis as template and oligodeoxynucleotides designed from conserved regions of various G protein alpha subunits we were able to amplify by the polymerase chain reaction two products of approximately 0.5 kb (P-1) and 0.8 kb (P-2). Sequencing showed that these two fragments share high homology with genes coding for the G alpha subunits from different sources. Using the P-1 fragment as a probe we screened a genomic library from K. lactis and we cloned a gene (KlGPA2) whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…lactis has at least two G-protein ␣ subunits that are involved in two different pathways. While KlGpa1p participates in the mating pathway, KlGpa2p is implicated in regulation of the adenylyl cyclase (25) and, as we showed here, is able to partially interfere with mating. These data suggest cross talk between these two proteins and, although we have not investigated a possible role of KlGpa1p in cAMP regulation, a relationship between cAMP and mating signaling pathways may exist.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…lactis has at least two G-protein ␣ subunits that are involved in two different pathways. While KlGpa1p participates in the mating pathway, KlGpa2p is implicated in regulation of the adenylyl cyclase (25) and, as we showed here, is able to partially interfere with mating. These data suggest cross talk between these two proteins and, although we have not investigated a possible role of KlGpa1p in cAMP regulation, a relationship between cAMP and mating signaling pathways may exist.…”
Section: Discussionsupporting
confidence: 64%
“…We have already demonstrated that one of these genes, KlGpa2, encodes a subunit directly involved in the regulation of cAMP levels in K. lactis (25). Cells lacking KlGpa2p are viable but fail to respond to transient stimulus by glucose and the cAMP level drops significantly, indicating that the G protein containing KlGpa2p is involved in regulating the activity of adenylyl cyclase and participates in a pathway related to monitoring the nutrient status of the cell (25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar function had been previously observed for G␣ proteins in Schizosaccharomyces pombe (Isshiki et al, 1992) and Kluyveromyces lactis (Saviñ on-Tejeda et al, 1996).…”
Section: Saccharomyces Cerevisiaesupporting
confidence: 85%